Declarative and procedural tactical knowledge in soccer players of different ages - D.S. Giacomini; V.O. Soares; H.F. Santos; C.J. Matias; P.J. Greco (Desafio Singular, 2011)
The quality of the performance on collective games is related to cognitive capacities, specifically to knowledge. This study verified the association between convergent and divergent procedural tactical knowledge as well as the association between declarative and procedural tactical knowledge. Participated in this study 221 male soccer players of U-14, U-15 and U-17 categories. The procedural tactical knowledge was assessed by KORA-OO on the parameters "offer yourself" and "self-orientation". The declarative tactical knowledge was assessed by soccer videos. Results revealed a clear association between convergent and divergent procedural tactical knowledge in general and per category and a low association between procedural (convergent and divergent) and declarative tactical knowledge. These data support the idea that knowledge progresses from declarative to procedural.